ORR Activity of Ru@Pt/C Core-Shell Nanosheets with a Flat Two-Dimensional Structure - Zhang, Junke; Muramatsu, Keisuke; Sugimoto, Wataru (Meeting abstracts (Electrochemical Society), 2024)
Two-dimensional metal nanosheets with atomic-level thickness have garnered widespread attention as electrocatalysts for the oxygen reduction reaction (ORR). The unique two-dimensional structure of nanosheets results in high atomic utilization and large specific surface area, while also exhibiting high durability, which is a significant characteristic of nanosheets. 1 However, the specific activity of monometallic nanosheets still does not meet the requirements of electrocatalysts for widespread commercialization of polymer electrolyte fuel cells. Core-shell structures hold promises to enhance the catalyst activity and durability. We have synthesized core-shell Ru@Pt/C nanosheets by sequentially depositing Pt atomic layers on the surface of metallic Ru nanosheets using the Surface Limited Redox Replacement (SLRR) method (Figure 1). 2 The Ru@Pt nanosheets exhibited 4 times higher ORR mass activity compared to commercial Pt nanoparticles. Such core-shell nanosheets serves as model catalysts for understanding the structure-property relationship in metal nanosheets. However, as the thickness of the shell increases, the roughness increased due to inhomogeneous deposition owing to the microstructure of the carbon support. In this study, core-shell Ru@Pt nanosheets with a flat surface architecture was synthesized by utilizing freeze-drying (FD) to suppress the deformation of the core Ru nanosheets. Ruthenium oxide nanosheets (RuO 2 (ns)) were exfoliated from a layered ruthenic acid. The RuO 2 (ns) colloid was mixed with carbon black and the mixture was freeze-dried to obtain RuO 2 (ns)/C-FD. RuO 2 (ns)/C-FD was reduced to metallic ruthenium nanosheets (Ru(ns)/C-FD) under H 2 gas flow at 200 o C. Transmission electron microscopy (TEM) image of RuO 2 (ns)/C-FD and the electrochemical active surface area (ECSA) of Ru(ns)/C-FD indicated the preservation of the flat morphology of the nanosheets on the carbon support. A flat Pt shell layer was uniformly deposited on the Ru(ns) core by SLRR. A monolayer of Cu was deposited on Ru(ns)/C-FD via Underpotential Deposition (UPD). UPD-Cu was then replaced with Pt. Coulometric measurements after UPD indicated an increase in charge of about 1.5 times the previous value, suggesting that 0.5 layers of Pt shell were deposited on the surface of Ru(ns) during each SLRR synthesis. Through repeatedly applying this SLRR process, Ru@Pt- n ML(ns)/C-FD ( n represents the number of Pt atomic layers) was synthesized. The roughness factor (RF) for Ru@Pt- n ML(ns)/C-FD ( n = 1.5, 2.5, 3.5), defined as the ratio of experimental ECSA values to theoretical ones, was 0.78, 1.25, 1.23, respectively. On the contrary, the RF for Ru@Pt- n ML(ns)/C-120 °C ( n = 1.5, 2.5, 3.5), prepared by thermal drying was 0.72, 1.85, 2.96, respectiely. 2 The restraint of RF increase in Ru@Pt- n ML(ns)/C-FD is attributed to the flat surface structures of Ru(ns)/C-FD which was achieved by suppressing the deformation of the core nanosheets through freeze-drying. The ORR activity in O 2 -sat. 0.1 M HClO 4 was evaluated using a rotating disk electrode. The mass activity for Ru@Pt-3.5ML(ns)/C-FD was only 1/2 of that Pt/C. This can be attributed to its lower ECSA caused by the flat surface, leading to a decrease in mass activity. The specific activities for Ru@Pt- n ML(ns)/C-FD ( n = 1.5, 2.5, 3.5) were 150, 356, 1033 μA cm -2 , respectively. The initial low activity is due to the electronic effect from the Ru core. Ru@Pt-3.5ML(ns)/C-FDexhibited specific activities close to that of pure Pt nanoparticles. (1) D. Takimoto, W. Sugimoto, Q. Yuan, N. Takao, T. Itoh, T. V. T. Duy, T. Ohwaki and H. Imai, ACS Appl. Nano Mater. , 2 , 5743 (2019). (2) D. Takimoto, T. Ohnishi, J. Nutariya, Z. Shen, Y. Ayato, D. Mochizuki, A. Demortière, A. Boulineau and W. Sugimoto, J. Catal. , 345 , 207 (2017). Figure 1